1998
DOI: 10.1051/forest:19980108
|View full text |Cite
|
Sign up to set email alerts
|

Estimating tree canopy water use via xylem sapflow in an old Norway spruce forest and a comparison with simulation-based canopy transpiration estimates

Abstract: -Tree xylem sapflow rates of 140-year-old Norway spruce (Picea abies) were scaled to the stand level and compared to canopy transpiration predicted by the stand gas exchange model STANDFLUX. Variation in sapflux densities between individual sensors was high (coefficient of variance = 0.4) and included both variation within and between trees, but it was not different between two applied sapflow methodologies (radial flowmeter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 37 publications
4
24
0
3
Order By: Relevance
“…Similar transpiration rates were found in studies on stands of Pinus sylvestris [25] and Picea abies [27]. Comparisons between the two systems installed in the same trees were made on Quercus petraea [20] and Picea abies [26].…”
Section: Introductionsupporting
confidence: 54%
“…Similar transpiration rates were found in studies on stands of Pinus sylvestris [25] and Picea abies [27]. Comparisons between the two systems installed in the same trees were made on Quercus petraea [20] and Picea abies [26].…”
Section: Introductionsupporting
confidence: 54%
“…Sap flow methods deal with methodological and integration problems (Köstner et al, 1998) that introduce uncertainty on the measurements. At the tree level, the most important error introducing factors are: non-uniformity of the sap flow along the radius (when radial pattern is neglected), determination of the sapwood depth, positioning of sensors beneath the cambium, possible non-parallelism of inserted needles, differences in xylem heath conductivity and temporal variations.…”
Section: Sap Flow Measurementsmentioning
confidence: 99%
“…Several authors found that the contribution of internal water to transpiration is not a constant in the water budget of trees (Loustau et al, 1996;Köstner et al, 1998;Zweifel et al, 2005;Verbeeck et al, 2007), but changes dynamically from day to day. To determine the complete water balance of a forest ecosystem and its dynamics, it is therefore important to know which factors influence the use of stored water.…”
Section: Introductionmentioning
confidence: 99%
“…Total [25] and Swanson [74]). HPV methods (early descriptions in Huber and Schmidt [47], Marshall [60] and Swanson [73] [54] and in the daily course of sapflow when both techniques are applied in parallel in the same tree (see figure 2). Com Granier [30,31] [69].…”
mentioning
confidence: 99%